26. UNICORNUATE UTERUS WITH A NON-COMMUNICATING RUDIMENTARY HORN: A RARE CLINICAL CASE REPORT AND MEDICAL LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2024)
Background: Müllerian duct anomalies are rare congenital malformations of the female genital tract. MDAs are estimated to occur in 1-5% of all women. There is a higher rate of women with repeated miscarriages (3-15%) [1]. According to the classification of Mullerian duct anomalies given by the American Society of Reproductive Medicine (ASRM) 2021, unicornuate uterus with a rudimentary non-communicating functioning horn is a subtype of 9 type of MDA, with an incidence of 0.06%, a rare Mullerian anomaly [3]. Accurate diagnosis of Müllerian duct anomalies (MDA) remains a clinical challenge [4]. This clinical case is introduced with the aim of re-discussing the management and monitoring of the disease.Clinical case: A 32 -year woman presented at our hospital with severe abdominal pelvic pain after spontaneous abortion two weeks ago. As a teenager, she had been suffering dysmenorrhea and increasing pain level by the time. On gynecology examination, left pelvic mass was measured 6 x 8 cm, tough, immobile. MRI showed evidence of unicornuate uterus in the left iliac fossa with blood stagnation. Surgical treatment with the resection of the rudimentary uterine horn, was carried out with good outcomes.Conclusion: Not only MDA but also unicornuate uterus with a rudimentary non-communicating functioning horn is a rare congenital uterine malformation. Chosing treatment option should be based on the severity of complications after discussing carefully with the patient and family to individualize the plan for each case.
Keywords: Müllerian duct anomalies, congenital uterine, unicornuate uterus, non-communicating horn.